2021
DOI: 10.2147/cmar.s281969
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Bone Morphogenetic Protein 2 Suppresses the Stemness Maintenance of Cancer Stem Cells in Hepatocellular Carcinoma via the MAPK/ERK Pathway

Abstract: Background Hepatocellular carcinoma (HCC) remains a life-threatening malignant tumor. Cancer stem cells (CSCs) harbor tumor-initiating capacity and can be used as a therapeutic target for human malignancies. Bone morphogenetic proteins (BMPs) play a regulatory role in CSCs. This study investigated the role and mechanism of BMP2 in CSCs in HCC. Methods BMP2 expression in HCC tissues and cells, and CSCs from HepG2 cells and SMMC7721 cells (HepG2-CSCs and SMMC7721-CSCs) wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 52 publications
2
5
0
Order By: Relevance
“…Leukemic BMPR1b high cells respond to BMP4 by amplifying and maintaining their CSCs population, whereas BMP2 favors the expansion of myeloid CML progenitors. A similar role for BMP2 in the maintenance of CSCs was recently reported in hepatocellular carcinoma ( Guo et al, 2021 ). In addition, BMPR1b mutations were linked to Brachydactyly type A1 characterized by bones hyperplasia, indicating that BMPR1b alterations could affect both the HSCs and MSCs in different physiopathological contexts by affecting their response to BMP4 ( Laperrousaz et al, 2013 ; Racacho et al, 2015 ).…”
Section: Introductionsupporting
confidence: 80%
“…Leukemic BMPR1b high cells respond to BMP4 by amplifying and maintaining their CSCs population, whereas BMP2 favors the expansion of myeloid CML progenitors. A similar role for BMP2 in the maintenance of CSCs was recently reported in hepatocellular carcinoma ( Guo et al, 2021 ). In addition, BMPR1b mutations were linked to Brachydactyly type A1 characterized by bones hyperplasia, indicating that BMPR1b alterations could affect both the HSCs and MSCs in different physiopathological contexts by affecting their response to BMP4 ( Laperrousaz et al, 2013 ; Racacho et al, 2015 ).…”
Section: Introductionsupporting
confidence: 80%
“…Zhang et al revealed that high-dose exogenous BMP-4 promotes the differentiation of CD133 + CSCs in HCC, whereas low-dose exogenous BMP-4 upregulates CD133 expression, suggesting a concentration-dependent effect of BMPs on CSC maintenance ( Zhang et al, 2012 ). Silencing of BMP-2 in HCC suppresses Erk MAP kinase and inhibits sphere formation and the expression of stemness-related and EMT markers in CSCs from HCC cell lines ( Guo et al, 2021 ). BMP-9 promotes CSC properties in epithelial cell adhesion molecule (EpCAM)-positive HCC subtypes by enhancing ID1 expression ( Chen et al, 2021 ).…”
Section: Effect Of Bone Morphogenetic Proteins On Cancer Stem Cellsmentioning
confidence: 99%
“…The expression levels of BMP-2/4 and ALK3 were upregulated in tumor tissues. Many of these are correlated with various clinical or biological parameters, such as unfavorable prognosis, tumor grade, TNM stage, vascular invasion, and the expression of the stem cell marker CD133 ( Guo D et al, 2012 ; Zhang et al, 2012 ; Ma et al, 2017 ; Feng et al, 2019 ; Li et al, 2020 ; Guo et al, 2021 ). Increased BMP-9 expression is also observed in HCCs and significantly associated with poor outcomes and the T stage of HCC ( Herrera et al, 2013 ; Li et al, 2013 ; Chen et al, 2021 ).…”
Section: Altered Expression Of Bone Morphogenetic Proteins and Their ...mentioning
confidence: 99%
“…As for BMP2, in the present study, patients with BCLC stage B-C had significantly higher BMP2 expression levels than patients with BCLC stage 0-A, suggesting the involvement of BMP2 in the progression and metastasis of HCC. Previous studies have demonstrated that BMP2 may promote HCC cell proliferation and invasion, thereby promoting malignant progression of HCC ( 20 , 21 , 44 ). As such, the results of the present study are in accordance with previously reported results.…”
Section: Discussionmentioning
confidence: 99%